Assessing the Service Quality of Prison Education in Cambodia: A Case Study of the 1st Correctional Center - Vicheka Reth; SENG Dararaksmey (Journal of General Education and Humanities, 2025)
Prison education plays a crucial role in rehabilitation, yet its service quality remains underexplored, particularly in Cambodia. This study examines the quality of prison education at the 1st Correctional Center, addressing a key research gap by evaluating prisoners’ expectations versus their actual perceptions of educational services. The objective is to assess whether current programs meet rehabilitative goals and identify barriers to effective education delivery. Using a mixed-methods approach, the study integrates quantitative surveys and statistical analysis with qualitative interviews to evaluate service quality comprehensively. A paired t-test analysis (t = 8.95, p < 0.001) revealed that prisoners rated education services higher than expected. However, limited resources, overcrowding, inconsistent policies, and a shortage of qualified educators still hinder effectiveness. Qualitative results further highlight institutional barriers, including security restrictions limiting prisoner participation and the lack of standardized curricula across facilities. Additionally, while education is recognized as a rehabilitative tool, its role in clemency decisions and sentence reductions remains ambiguous, underscoring the need for policy enhancements. These findings contribute to ongoing prison reform efforts, highlighting the importance of inter-agency collaboration, digital learning expansion, and integrating education into legal reintegration frameworks. By addressing structural challenges and aligning prison education with global best practices, Cambodia can strengthen its correctional education system, ultimately improving prisoner rehabilitation and reintegration.